2017
DOI: 10.1088/2058-6272/aa5fc6
|View full text |Cite
|
Sign up to set email alerts
|

One-step phenol production from a water–toluene mixture using radio frequency in-liquid plasma

Abstract: The objectives of this research were to understand the process of converting toluene into phenol in a one-step process directly from a water-toluene mixture using the plasma in-liquid method. Experiments were conducted using 27.12 MHz radio frequency (RF) in-liquid plasma to decompose a solution of 30% toluene. Based on the experimental results as evaluated using gas chromatography-mass spectrometry (GC-MS), along with additional analysis by the Gaussian calculation, density functional theory (DFT) hybrid exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Ogasawara and Wu reported that formic acid is the main by‐product in the exhaust of NTP‐treated toluene. Furthermore, benzene, benzaldehyde, benzyl alcohol, and benzoic acid have been identified on the catalyst surface . In addition, acetone, acetic acid, and formaldehyde have also been identified in the NTP decomposition of toluene .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Ogasawara and Wu reported that formic acid is the main by‐product in the exhaust of NTP‐treated toluene. Furthermore, benzene, benzaldehyde, benzyl alcohol, and benzoic acid have been identified on the catalyst surface . In addition, acetone, acetic acid, and formaldehyde have also been identified in the NTP decomposition of toluene .…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, benzene, benzaldehyde, benzyl alcohol, and benzoic acid have been identified on the catalyst surface. [46][47][48] In addition, acetone, acetic acid, and formaldehyde have also been identified in the NTP decomposition of toluene. 49 According to these previous results, CH 2 In the subsequent experiments, the gas-phase organic by-products were quantified by PTR-TOFMS to give a more precise evaluation of the NTP technique.…”
Section: Study Of Toluene Removal By Ntpmentioning
confidence: 99%
“…Toluene hydrogen peroxide undergoes rearrangement reaction under acidic conditions to generate phenol and formaldehyde gas. 30 Hydroxyl radicals can also be produced in the reaction process as secondary oxidation species to react with toluene to produce phenol 32…”
Section: Acs Sustainablementioning
confidence: 99%